All the colors of the dark : a novel [large type] - Whitaker, Chris (Read with Jenna., 2024)
"From the New York Times bestselling author of We Begin at the End comes an epic novel about a man fixated on finding a missing woman and the FBI agent on his tail, who might be even more obsessed than he is"--